Analysis Implementation of Sharia Economic Dispute Resolution In Non-Litigation Through BASYARNAS (Indonesian National Syariah Arbitration) - Muhammad Abdul Aziz; Imam Kamaluddin; Mohammad Ghozali; Siti Marpuah; Syarifah Normawati (Advances in Humanities and Contemporary Studies, 2023)
This article reviews non-litigation dispute resolution by arbitration through BASYARNAS. Researchers conducted field research with qualitative methods and empirical approaches. The data used are primary data and secondary data. After all the data is collected, then the data is reduced and submitted by drawing conclusions and verification, and processing it in an inductive way. Qualitative research methods are used to analyze the object under study. Then conclusions are drawn with a descriptive description. Based on the results of the research conducted, the settlement of sharia economic disputes through BASYARNAS is still of minimal interest because of the executorial power factor, absolute authority factor and the existence factor, the majority of BASYARNAS is only in the capital, and even then in some provinces in Indonesia. BASYARNAS has advantages in terms of written law, but in the implementation of justice it is necessary to improve the quality of judges, their presence which is easily accessible by each district, and the culture of the community that runs. So it can be concluded that BASYARNAS has not been effective in resolving sharia economic disputes for the reasons that have been stated